2014
DOI: 10.1186/s13052-014-0094-2
|View full text |Cite
|
Sign up to set email alerts
|

“Risk factors of birth asphyxia”

Abstract: BackgroundBirth asphyxia is an insult to the fetus or newborn due to failure to breath or breathing poorly, leads to decrease oxygen perfusion to various organs. According to WHO, 4 million neonatal deaths occurred each year due to birth asphyxia. Our goal was to evaluate antepartum, intrapartum, and fetal risk factors of birth asphyxia.MethodsIt was a Retrospective Case control study, conducted at Neonatal Intensive Care Unit of pediatric ward (I, II, III) and in Gynecology wards (I, II, III) of Civil Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

43
138
5
19

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(232 citation statements)
references
References 8 publications
43
138
5
19
Order By: Relevance
“…Like some other studies we found low birth weight was a significant factor for causing birth asphyxia 1,12 . In this study, meconium stained amniotic fluid was found > _ to be present as one of the risk factor, findings were comparable with previous study also 1,12 .…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Like some other studies we found low birth weight was a significant factor for causing birth asphyxia 1,12 . In this study, meconium stained amniotic fluid was found > _ to be present as one of the risk factor, findings were comparable with previous study also 1,12 .…”
Section: Discussionsupporting
confidence: 51%
“…But low socioeconomic status was significantly associated with PNA. In our study young maternal age (20-25 years) and primigravidity emerged as one of the main risk factors of developing birth asphyxia as mentioned in previous studies 1,12,24,29,30 . We found birth asphyxia was significantly high in termed delivery than preterm babies which was also reported in some past studies 13,21 .…”
Section: Discussionmentioning
confidence: 55%
“…The combination of hypoxia and ischemia results in clinical and biochemical changes, which lead to multiorgan cell damage including neuronal cell death and brain damage. 1 Continuous asphyxia will also lead to multiple organ and systems dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Perinatal asphyxia is a serious clinical problem worldwide and contributes greatly to neonatal mortality and morbidity. 1,3,4 Diagnosis of asphyxia is usually made on the clinical criteria. The most frequent abnormalities involved are found in kidneys, respiratory, central nervous and cardiovascular systems.…”
Section: Introductionmentioning
confidence: 99%
“…Perinatal asphyxia happens in 2 to 10 per 1000 newborns that are born at term, and more for those that are born prematurely. 1 WHO estimates that 4 million neonatal deaths occur yearly due to birth asphyxia, representing 38% of deaths of children under 5 years of age. 2 Perinatal asphyxia can be the cause of hypoxic ischemic encephalopathy or intraventricular hemorrhage, especially in preterm births.…”
mentioning
confidence: 99%